ANALISIS PENGARUH LOCUS OF CONTROL DAN SELF EFFICACY TERHADAP KINERJA DENGAN ETIKA KERJA ISLAM SEBAGAI VARIABEL MODERATING (Study Empiris pada Perawat di Rumah Sakit Islam Sultan Agung Semarang) (Proceeding Fakultas Ekonomi, 2015)
This research aims to analyze the influence of Islamic work ethichs toward the relationship of Locus of Control and Self Efiicacy toward nurses performance. The writer uses purposive sampling method to take the sample from Sultan Agung Islamic Hospital Semarang. The data tested in this research covers validity test with product moment, reliability test with alpha cronbach, multiple linear regression analysis, t-test for testing and proving the research hypothesis.Result from regression analysis t-test shows that (1) Locus of Control has influence toward performance, as strong as Locus of Control influence inside the nurse the nurse self,, her performance increases (2) Self Efficacy has influence toward performance, as strong as self efficacy influence inside the nurse self, her performance increase, (3) Locus of Control variable is as moderating variable, enhancement of Locus of Control suppearted by Islamic, (4) Self Efficacy variabel is not moderating variabel reduction of self Efficacy supported by Islamic work ethics will reduce the nurse performance.Keywords : Locus of Control, Self Efficacy, Islamic Work Ethics , Performance